Characterization of a tumor necrosis factor alpha (TNF-alpha) inhibitor: evidence of immunological cross-reactivity with the TNF receptor. - Seckinger, P (1990)
Previous studies have shown that urine of febrile patients contains a tumor necrosis factor alpha inhibiting activity (TNF-alpha Inh) when tested in a cytotoxicity assay using the tumor necrosis factor alpha (TNF-alpha)-susceptible cell line L929. In the present study, we investigated the relationship between the TNF-alpha Inh and a potential soluble form of the receptor, as the former has been shown to block TNF-alpha activities by binding to the ligand. We demonstrate that human TNF-alpha is affected to a greater extent than is murine TNF-alpha. This species specificity of the inhibitor correlates with the binding studies of TNF receptor interactions already reported. We raised a polyclonal antibody to TNF-alpha Inh that neutralizes its activity and does not recognize TNF-alpha. Solubilized cross-linked 125I-labeled TNF-alpha receptor complex could be immunoprecipitated by using either anti-TNF-alpha or anti-TNF-alpha Inh antibody, suggesting immunological cross-reactivity between the receptor and the inhibitor. By using fluorescein isothiocyanate-coupled TNF-alpha, it was possible to visualize by fluorescence-activated cell sorter analysis the TNF-alpha receptor on phytohemagglutinin/interleukin 2-activated T cells. A similar increase of immunofluorescence intensity of the activated T cells was observed by using anti-TNF-alpha Inh antibody revealed with a fluorescein isothiocyanate-coupled goat anti-rabbit IgG1 conjugate, suggesting that the TNF-alpha Inh is also expressed as a membrane protein. Taken together, our results suggest that the TNF-alpha Inh originally described might be a soluble form of the TNF receptor itself.